Принцип верховенства права як основа розвитку правової держави та громадянського суспільства - Денисюк, М.В. (Альманах права, 2012)
У статті аналізується зміст поняття «верховенство права» та «правова держава», а також визначено співвідношення цих феноменів. В статье анализируется содержание понятия «верховенство права» и «правовое государство», а также определено соотношение этих феноменов. The issue of formation legal state and civil society belongs to a group of fundamental questions not only of classic but also of modern scientific theory of law. The state may be stated as legal if the basis for its operation will be the law that guarantees rights and freedoms of citizens, limits the state, the public authority carried out on the rule of law and separation of power. The rule of law takes the central position in the description of legal state. The rule of law is definitely an expression of universal values, a manifestation of cultural development. There are different approaches, dimensions and aspects of the study to the rule of law in legal theory. The rule of law and legal state are value categories, humanistic ideals of society. However, the correlations between these phenomena were not investigated properly. Some scientists believe that the definition of rule of law is wider than legal state and in this sense means that the law should prevail in civil society, in the state and its legal system. It should cover all areas of human life including the international sphere. Other scientists narrows it to the legal state and the third doesn’t see the fundamental difference between English «Rule of law» and German «Rechtsstaat». So establishing the rule of law in our country and functioning of a democratic, legal state possible only under such conditions: existence of a vibrant civil society; implementing the principle of popular sovereignty; separation of state power, consolidation of human rights and freedoms in the Constitution; the principle of fundamental rights and freedoms is real; implementing the principle supremacy of the Constitution; state’s responsibility before personality; adherence to the principle of legal certainty; law enforcement etc. Thus the rule of law is a priority of the highest human values in all spheres of public life, the road to world order.